2018
DOI: 10.1111/jmg.12291
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments and the future of low‐T calorimetric investigations in the Earth sciences: Consequences for thermodynamic calculations and databases

Abstract: Low-T calorimetry is an experimental science that measures the thermodynamic function heat capacity, C p (T), from which the standard third-law entropy (298.15 K), S°, is calculated. The recent technological development of relaxation calorimetry allows both new experimental strategies and types of C p investigations to be made, which were previously not possible. The C p measurements are fast and automated and can be made on mg-sized mineralogical samples between 2 and 400 K. These advantages, when careful mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…As C p below 2 K (−271.15°C) has low absolute values <0.3 J/(mol·K), the entropy increment from 0 to 2 K (−273.15 to −271.15°C) was neglected. As outlined in Ref, standard entropy determinations, based on PPMS‐measured C p data, can be expected to be accurate to within 0.5%. A graphical representation of the data is given in Figures 5 and 6.…”
Section: Experimental Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…As C p below 2 K (−271.15°C) has low absolute values <0.3 J/(mol·K), the entropy increment from 0 to 2 K (−273.15 to −271.15°C) was neglected. As outlined in Ref, standard entropy determinations, based on PPMS‐measured C p data, can be expected to be accurate to within 0.5%. A graphical representation of the data is given in Figures 5 and 6.…”
Section: Experimental Methodsmentioning
confidence: 94%
“…Furthermore details on the PPMS measurements and evaluation procedures can be found, for example, in and will not be repeated here. Experimental uncertainties associated with this method are discussed in Ref …”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Converting vol.% to mol%, we obtain 6.7 mol% wollastonite and 93.3 mol% andradite, and taking a value of S°= 163.4 J/mol · K for wollastonite (Robie & Hemingway, 1995), we obtain a final corrected S°value of ∼330 J/mol · K ( Table 4). The S(T) behavior for andradite from 0 K to 298 K is given in Geiger & Dachs (2018). It shows that S(T) is underestimated by the Robie et al (1987) results at about T < 13 K and slightly overestimated at roughly T >50 K. Finally, in another early calorimetric investigation, Kiseleva et al (1972) reported S°value of 329.28 ± 5.4 J/mol · K (Table 4).…”
Section: Magnetic Phase Transitionmentioning
confidence: 89%
“…The closer the sample coupling is to 100%, the better the thermal conductance between the sample platform and the sample, which ensures a more robust heat-capacity determination via relaxation calorimetry. Experience indicates that an accuracy of about 0.2 (or even 0.1)% above ∼30 K in C p and the standard entropy, S°, can be achieved for single crystals (Benisek & Dachs, 2008;Dachs & Geiger, 2018). It is between about 0.2% and 0.5% for measurements on powders (weighing about 10-20 mg) contained in thin Al-metal foil.…”
Section: Uv/vis Optical Absorption Single-crystal Spectroscopymentioning
confidence: 98%